ANÁLISE DOS INDICADORES DE GESTANTES DO PROGRAMA PREVINE BRASIL NO MUNICÍPIO DE BACABAL - MA - LIMA, Janaina Borges Silveira (2024)
Introduction: Prenatal care is part of the strategic actions in the field of Women's Health in Primary Care, being extremely relevant for the promotion of maternal and child health, which justifies the importance of monitoring and evaluation processes through the Previne Brasil Program. Objective: To analyze the indicators related to pregnant women assisted by the Previne Brasil Program by the Family Health teams (eSF) in the municipality of Bacabal/MA. Method: Ecological study, using secondary data of indicators related to pregnant women obtained from 2020 to 2023. The indicators listed were: proportion of pregnant women with at least six prenatal consultations, the 1st (first) being up to the 12th (twefth) week of gestation; proportion of pregnant women who were tested for syphilis and HIV; and proportion of pregnant women with dental care. Results: The trend in the proportion of pregnant women with at least six prenatal consultations was increasing in most Family Health teams, both in urban and rural areas; the team with National Team Indicator (INE) 43184, from the Esperança Health Center, had the highest rate of change (28.75). In the indicator referring to the proportion of pregnant women who underwent tests for syphilis and HIV, most of the teams in the rural and urban areas also showed an increasing trend, with the team with INE 43109, from the Areal Neighborhood Health Center, standing out, which obtained the highest rate of change (29.43). Regarding the indicator related to the proportion of pregnant women with dental care, only most of the teams in the urban area showed an increasing trend, while in the rural area, most of the teams showed a stable trend. However, the team with INE 1531425, from the Brejinho Health Center, in the rural area, showed an increasing trend with the highest rate of variation (55.40). None of the teams showed a downward trend in any of the indicators analyzed. Final considerations: Most of the eSF showed an increasing trend in the indicators analyzed and for the improvement of the indicators of the eSF with a stable trend, it is relevant to implement more effective actions, both in the scope of health practices and services and in management, aiming at positive impacts on prenatal care for pregnant women in the municipality.